(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The natural changes in the vegetation of the valley in the estuary are represented by syngenetic (primary and secondary), endoecogenetic geomorphic succession series. The processes of syngenesis and endocechenesis greatly developed in recent decades. It connect with catastrophic decline of the estuary area and the formation of new terrestrial territories. In the initial stages of overgrown, these territories colonized by pioneer halophytes, which initiate succession from the Salicornia perennans agglomerations to Artemisietum santonicae communities. The paper presents the peculiarities of the initial succession in vegetation occurring on different estuary coastal areas. Secondary overgrowth of quarries on the estuarine spit and coastal areas are occurring with the participation of the ruderal species (including adventive). It is areas where vegetation destroyed by melioration works. Natural vegetation are not renewed on these territories under new conditions. Geomorphic successions are associated with the mobility of the substrate on the valley sloping areas. It has an extremely strong influence on the formation of steppe vegetation in these territories. The slow regressive geomorphic changes are most widespread. It lead to the replacement of zonal steppe communities with desert-steppe and halophytic-steppe. The catastrophic geomorphic changes are characteristic for very steep clay slopes. The restoration of vegetation on the aspirations begins with the weed stages and passes in towards the formation of steppe and shrub communities.